Garabato y creatividad en niños de tres y cuatro años en la Institución Educativa Inicial Santa Rosa de Lima, San Juan Bautista 2019 - Moreno Vargas, Marianella Katherine (2022)
In 2019, this research was carried out to relate scribbling and creativity in three and four-year-old children of the Santa Rosa de Lima Initial Educational Institution, located in the district of San Juan Bautista. For this purpose, the type of relational research was used as a methodology, with a bivariate, field, and cross-sectional design. The population for this study consisted of 100 children aged three and four from the educational institution. The observation technique has been used and it was applied as observation guide instruments for data collection, which were validated by experts. After analyzing the findings, it is concluded that between the doodle variable and creativity in children aged three and four from the I.E.I. Santa Rosa de Lima, there is a strong and significant direct relationship because Spearman's rho correlation coefficient is= 0.694**; and p value is = 0.000.